The Effectiveness of Using Wordwall Media in Learning English Vocabulary Mastery at the Tenth-Grade Students of SMAN 14 Bone - Fatimah Alsyahrah; Andi Suwarni; Syarifuddin Syarifuddin (Journal on Education, 2025)
This research aimed to enhance the effectiveness of English learning to improve students' English vocabulary through Wordwall media. It employed a quantitative method with a pre-experimental approach, using a one-group pretest-posttest research design. The research was conducted with students of class X.3 at SMAN 14 Bone. The sample consisted of 34 students selected from a population of 243. Data collection was carried out through pre-tests and post-tests, with the average score being 43.09 and the average post-test score being 85.88. Based on these results, there was an increase of 42.79 in the average scores. The results indicated that the Sig. (2-tailed) value was 0.000 < 0.05, demonstrating a significant improvement in students' scores after the implementation of learning using Wordwall media. This research proved to be effective in improving students' English vocabulary, as evidenced by the results of the N-Gain test, which showed an average value of 0.77 > 0.70.